"Girls have commercial sex, boys don't:" Mixed-methods evidence for a gendered risk environment for street-connected young people in the Republic of Georgia. Issue 2 (3rd April 2022) - Sadzaglishvili, Shorena; Gotsiridze, Teona; Lekishvili, Ketevan; Verdino, Anthony P.; Flores, Rey; Bouris, Alida
Abstract: Street-connected young people (SCYP) in the Republic of Georgia are vulnerable to HIV/AIDS. We conducted a mixed-methods study utilizing a triangulation design with N  = 20 SCYP aged 11–18 (50% female; M = 13.95 years; SD = 2.11) recruited from two cities in Georgia. SCYP completed a close-ended survey and an in-depth interview on their perceptions of romantic and exchange sex relationships. Quantitative analyses examined gender differences in perceptions of romantic and exchange sex partners, and qualitative data was analyzed using a thematic analysis approach. Quantitative findings indicated that a higher proportion of female than male SCYP endorsed engaging in HIV-related transmission behaviors with exchange sex partners. Thematic analysis contextualized survey findings by elucidating the ways in which females negotiated a highly gendered risk environment that elevated their vulnerability to HIV. Study results highlight the need for gender-responsive programming to address the HIV prevention needs of both male and female SCYP in the Republic of Georgia.